Peran International Labour Organization (ILO) Melalui Proyek PRIDE Dalam Mengupayakan Kesetaraan Hak Kaum LGBT Di Thailand Tahun 2012-2015 - Wilantari, Made Rai Puspa; Kumala Dewi, Putu Ratih; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
Thailand is one of the countries that has promoted its country as a gay paradise country. Unfortuntely, this LGBT-friendly image is not what that image depicts. LGBT people in Thailand often experience acts of inequality and even discrimination by their surrounding peoples. The ILO is trying to take on its role as an international organization in helping LGBT people in Thailand to get the rights they deserve. Therefore, this study aims to explain the roles of ILO in efforting equal rights for LGBT people in Thailand through the PRIDE project conducted in 2012-2015. By using the concepts of the Role of International Organizations and Human Rights, the researcher found that ILO taking three roles with pre-determined standards, and used it as a basis for evaluating the Thai government through the collaboration that has been carried out with the actors involved. Keywords: equal rights, ILO, LGBT, PRIDE, Thailand